Coping, executive functioning, inhibitory control and decision-making in a sample of depressed suicidal patients - Medeiros, Tiago; Lopes, Emanuela; Macedo, Gerly; Monteiro, Luis (Clinical and Biomedical Research, 2014)
Introduction: Suicidal behavior has been associated with several risk factors, including depression, maladaptive coping, and neuropsychological dysfunction. This study aimed to evaluate coping orientations, executive functioning, attentional capabilities and decision-making in depressed suicidal patients. Methods: Two groups were selected: 32 depressed patients with history of suicide attempt and 30 depressed patients without history of suicide attempt. The Beck Depression Inventory and the COPE Inventory scales were applied, as well as the following neuropsychological tests: Wisconsin Card Sorting Test, Stroop Test, and a modified Iowa Gambling Task. Results: The results indicate a higher level of dysfunction in the executive functioning, mental control, and decision-making domains, and lower levels of orientation to active and reflective coping strategies, humor, and positive signification in the suicidal group. Conclusions: These results indicate that there are neuropsychological differences between depressed patients with and without history of suicide attempt, which may contribute significantly to the occurrence of suicidal behavior. However, the processes involved and the way they contribute to the phenomenon are aspects that still need further clarification.